THE EFFECTS OF LEARNING MOTIVATION AND CONFIDENCE TOWARDS ENGLISH SPEAKING SKILL - Roy Nor Dani; Sepeno Supeno (Universitas Indraprasta PGRI, 2018)
The aims at this research are (1) to find out the effect learning motivation and confidence towards English speaking skill of SMPN students at Karawang regency. (2) To find out the effect of learning motivation towards English speaking of SMPN students at Karawang reegency. (3) To find out the effect of students confidence towards English speaking of SMPN students at Karawang reegency. This research is survey on SMPN at Karawang regency, academic year of 2017/2018. The sample consists of 90 students who choosen randomly from several SMPN at Karawang regency. Taking data are carried out by distributing quisioner. Data analysis use descriptive statistic method, validity test, realibility test, multiple regression analysis. The results of this research are (1) There are simultaneouslu effects of learning motivation and confidence towards English speaking of SMPN students at Karawang reegency. It is proven by getting sig score 0,000<0,05 and Fcount = 64,715. (2) There is a significant effect of learning motivation towards English speaking of SMPN students at Karawang regency. It is proven by getting sig score 0,000<0,05 and Tcount = 7,256. (3) There is a significant effect of confidence towards English speaking of SMPN students at Karawang regency. It is proven by getting sig score 0,002<0,05 and Tcount = 3,191 Key Words: Learning motivation, Confidence, English speaking skill